Correlation between threading dislocations in highly mismatched GaN heteroepitaxial layers. (December 2017) - Romanitan, Cosmin
Abstract: A simple model that establishes a quantitative measure for the positional correlation degree of threading dislocations (TDs) in heteroepitaxial layers is proposed. Accordingly, analyzing the linewidth of the Gaussian fit that follows the experimental rocking curve (RC), we obtained the correlation degree of screw and edge TDs in GaN epitaxial layers grown on sapphire substrate. Calculating the numerical integral using both the standard Wilkens correlation parameter, M, and the new one, S, and comparing the numerical results with the experimental diffraction patterns for three samples of GaN epitaxial films with different thicknesses, we demonstrate that the newly determined correlation parameter is correct. Abstract : Highlights: A simplified method was proposed to obtain threading dislocations correlation degree using XRD data. A new parameter – S – was obtained and validated for GaN/sapphire heteroepitaxial layers. The S parameter is a quantitative measure of the positional correlation between threading dislocations. The method might be applied to high mismatch heteroepitaxial systems and to heterostructures with based on ternary compounds.